School council: functions, problems and perspectives in democratic school management - Ângelo Ricardo de Souza (Universidade Federal de Santa Catarina, 2010)
This article has a bibliographic nature and discusses the democratic problems and perspectives for school councils. The study fi rst discusses the problems of "mythifi cation" of technique in the constitution and use of school management organizing mechanisms. The text then demonstrates how the democratic functions and potential of the school council counter the daily diffi culties to constitute, maintain and develop collective spaces of management, demonstrating how much the councils are, in principle, spaces of dialog, and at the same time, how far they are from effectively exercising their democratic function. The conclusions point to the important recognition of the existing limits in the formulation and organization of school councils, but, at the same time suggest the need to insist on the maintenance and perfection of the councils because they represent a signifi cant contribution for democratic school management.